Ayoko ng Plastik exploring the influence of attitudes, norms, and perceived behavioral control on the single-use plastic avoidance behavior of Filipinos - Ferraris, Maria Felicia D.
The overconsumption of single-use plastic (SUP) in the Philippines has resulted in a plastic pollution crisis leading to frequent flooding, risks to human health, and threats to marine biodiversity. In response, Filipinos adapted single-use plastic avoidance behavior (SPAB), such as the use of ecobags, to minimize their SUP consumption.